Investigating Phonological Errors in the Pronunciation of English Vowel Diphthongs Among Fourth-Grade Students at Al-Kautsar Islamic Modern Boarding School - Mardi, Sumardi; Rugaiyah, Rugaiyah; Thayib Pido, Nur Wahidah (Journal of English Teaching and Linguistic Issues (JETLI), 2025)
This research aims to analyze the phonological errors made by fourth-grade students at Al-Kautsar Islamic Modern Boarding School in pronouncing English vowel diphthongs. A descriptive qualitative method was applied to explore students’ pronunciation by analyzing their recorded speech. The participants were five students from class IV-C during the 2024/2025 academic year. Each student performed a speech that was recorded and evaluated using phonetic software based on International Phonetic Alphabet (IPA) standards. The results demonstrated that students often had difficulties pronouncing diphthongs such as /eɪ/ and /oʊ/, largely due to interlingual influences (native language interference) and intralingual issues (complexity of the English language and unfamiliar phonological structures). It was observed that the diphthongs /aɪ/, /eɪ/, and /oʊ/ appeared frequently in the students’ speech, while others like /eə/ and /ʊə/ were either rare or absent. This absence is attributed to the prevalent use of American English pronunciation, which does not frequently utilize these diphthongs. The analysis revealed various levels of proficiency among the participants, with scores ranging from poor to good. These findings underline the importance of enhancing phonological awareness and pronunciation training among EFL learners. The study concludes with practical suggestions for improving pronunciation instruction through phonetics-based activities and greater exposure to native-like speech.